A study on the satisfaction level of selected public users in terms of physical design components in a Municipal Hall - Rabino, Kathlene L.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT The purpose of this research was to study the satisfaction levels of selected public users in a municipal hall's physical design components such as space planning, way-finding, ventilation, lightning, and accessibility. It focused on how age and gender affected their satisfaction levels with the emergence of influential factors including necessity, comfort, and preference. The study utilized a quantitative descriptive case study to understand conditions on a single subject matter with the help of frequency to establish results. The study used observation, photo-documentation, and questionnaires accomplished by selected respondents in a municipal hall as instrumentation. Through purposive sampling, the researcher gathered (40) forty respondents divided into (4) four groups of (10) ten individuals divided according to the NIF Annotation Standards for Age Classification for humans such as Young (0-18 years old), Early Adult (18-39 years old), Middle Adult (39-59 years old), and Aged (61 years old and above) with equal number of males and females per group. The key findings of the study revolve around the effect of age and gender on the satisfaction levels of selected public users in a municipal hall. Specifically, influential factors such as necessity, comfort, and preference emerged. However, while these factors affected the satisfaction levels of all age groups and genders of the selected public users, age appeared to be more influential than gender.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Municipal buildings -- Philippines -- Designs and plans